Extrafollicular Plasmablasts Present in the Acute Phase of Infections Express High Levels of PD-L1 and Are Able to Limit T Cell Response - Serrán, Melisa Gorosito; Vernengo, Facundo Fiocca; Almada, Laura; Beccaria, Cristian G.; Gazzoni, Yamila; Canete, Pablo F.; Roco, Jonathan A.; Boari, Jimena Tosello; Ramello, Maria Cecilia; Wehrens, Ellen; Cai, Yeping; Zuniga, Elina I.; et al. (Frontiers in Immunology, 2022)
During infections with protozoan parasites or some viruses, T cell immunosuppression is generated simultaneously with a high B cell activation. It has been described that, as well as producing antibodies, plasmablasts, the differentiation product of activated B cells, can condition the development of protective immunity in infections. Here, we show that, in T. cruzi infection, all the plasmablasts detected during the acute phase of the infection had higher surface expression of PD-L1 than other mononuclear cells. PD-L1hi plasmablasts were induced in vivo in a BCR-specific manner and required help from Bcl-6+CD4+T cells. PD-L1hi expression was not a characteristic of all antibody-secreting cells since plasma cells found during the chronic phase of infection expressed PD-L1 but at lower levels. PD-L1hi plasmablasts were also present in mice infected with Plasmodium or with lymphocytic choriomeningitis virus, but not in mice with autoimmune disorders or immunized with T cell-dependent antigens. In vitro experiments showed that PD-L1hi plasmablasts suppressed the T cell response, partially via PD-L1. Thus, this study reveals that extrafollicular PD-L1hi plasmablasts, whose peaks of response precede the peak of germinal center response, may have a modulatory function in infections, thus influencing T cell response.